Analisis Elastisitas Silang Pada Produk Kentang dan Jagung serta Dampaknya Terhadap Inflasi Daerah di Kecamatan Tarogong Kidul - Macharani, Shinta; Septya, Seny; Febriani, Shafira; Hakim, Firman; Murwenie, Ira (JURNAL EKONOMI, MANAJEMEN, BISNIS, DAN SOSIAL (EMBISS), 2025)
This research aims to analyze the cross-elasticity relationship between potato and corn products as one of the factors that reflects inflation in staple foods in Tarogong Kidul District, Garut Regency. The approach used is a quantitative descriptive method with a focus on associative analysis. Data was collected through observation and interviews, then processed using simple linear regression analysis and cross elasticity analysis. The research results show that changes in corn prices significantly affect potato demand at a significance level of 1%. Based on price elasticity analysis, the price of potatoes is inelastic to the demand for potatoes. Cross elasticity analysis shows that corn is a complementary good. In addition, this research shows that the increase in the price of potatoes and corn can be used as a marker of inflation, which has an impact on reducing public consumption and decreasing the income of traders and potato or corn farmers.